Analysis of Framer Income from Honey Bess (Apis cerana) in Tobo Ino Vilage, East Wasile Subdistrict, East Halmahera Regency - Yahya, Hadinda; Salim, Tamrin; Julham, Muhammad (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2024)
This research was carried out for one month starting from April 2024 to May 2024. The location of this research is in Tobo Ino Village, East Wasile District, East Halmahera Regency. The purpose of this study is to analyze farmers' income from honey bees (Apis Cerana) in Tobo Ino Village, East Wasile District, East Halmahera Regency. The respondents in this study were 3 people. The methods used in this study are observation, interviews and documentation. The data taken in this study are primary and secondary data. Based on the results of the study, it can be concluded that the income of Apis Cerana honey bee farmers in Tobo Ibo Village, East Wasile District, East Halmahera Regency from 3 existing respondents, has an income value of Rp 6,756,000 per year, with an average income of each respondent from Apis Cerana honey bees of Rp 2,252,000 per year.